Ovulation induction with human chorionic gonadotropin (hCG) and gonadotropin releasing hormone (GnRH) in mares - ATAMAN, M BOZKURT; GDNAY, A YTEKIN; UZMAN, MEHMET; GUNAY, DLGEN (The Indian Journal of Animal Sciences, 2014)
In this study, the efficacy of human chorionic gonadotropin (hCG) and gonadotropin releasing hormone (GnRH)administered to advance the ovulation in oestrous in mares was examined. Thoroughbred mares (36) were divided into 3groups. After the detection of (35 mm follicle in diameter, with the use of ultrasound, 3000 IU ho, 40mg btlsereline,GnRH and 2 ml placebo were injected to the mares in groups 1, 2 and 3 respectively. Follicles were monitored every 12hr with ultrasonography until the occurrence of ovulation. The mares were mated naturally every other day by the end ofoestrus. Pregnant mares were determined using B-mode real time ultrasound on day 20 after last mating. There was astatistical significance of(P